Computational prediction of the long-term behavior of the femoral density after THR using the Silent Hip stem. Issue 4 (12th March 2023) - Al-Hajaj, Zainab; Avval, Pouria Tavakkoli; Bougherara, Habiba
Abstract: Aseptic loosening due to the progressive periprosthetic bone resorption following total hip replacement is a crucial concern, that causes complications and failure of the arthroplasty surgery. The mismatch in stiffness between the hip implant and the surrounding femoral bone is one of the key factors leading to bone density resorption. This paper aimed to investigate the long-term response of the femoral bone after THR using the Silent Hip stem. For this purpose, a validated thermodynamic-based computational model was used to compute the change in bone density before and after THR. This model incorporated essential factors involved in bone remodeling process, such as mechanical loading, and biochemical affinities. The results of the numerical simulations using 3D finite element analysis were analyzed in five zones of interest qualitatively and quantitatively. Bone density predictions showed notable bone resorption in cervical areas, specifically in zone 1 and zone 5 of −18.7% and −14%, respectively. Conversely, bone formation was observed in the greater trochanter area (zone 2) of +25%. Stress shielding seemed to occur at cervical area due to the reduction in the mechanical loading in this region. Based on the quantitative analysis of the bone density distribution throughout the femoral bone, it appears that the Silent Hip stem achieved less bone resorption compared to conventional hip stem designs reported in the literature, which could be used for active patients.